Coke-assisted microwave ignition and combustion behaviors of anthracite in a switching atmosphere. (15th May 2022) - Su, Yanlin; Zhou, Wei; Li, Junfeng; Zhang, Lei; Gao, Jihui; Wang, Pengxiang; Qin, Yukun
Graphical abstract: Highlights: Tiny spark discharges trigger the rapid microwave heating on mixed coke and anthracite. The extra CO gasification remedies the shortage of volatile matter in anthracite to a certain extent. The intensive discharge with plasma in centimeter-scale promotes flame combustion. The distribution of coke in the mixture for effective ignition is preliminarily explored. Abstract: Low volatile coal has a large reserve but faces significant challenges in industrial applications. Due to the rapid and selective heating process, microwave-based technology is generally applied in various studies of carbonaceous materials. This work verified a novel non-contact microwave ignition of anthracite mixed with coke, where typical events of ignition or combustion were recorded by a digital camera. Video image analysis showed that the weakening of O2 to the tiny spark discharges between coke particles failed microwave heating. Hence a switching atmosphere (100% N2 firstly, then O2 at a certain proportion added) was used to ensure rapid microwave heating and subsequent ignition. Ignition of mixed anthracite & coke took place in the middle of the sample once the volatile flame appeared, which following the sample locally turned red-hot. The time for the flame burning was prolonged by the microwave power and especially the increase of O2 proportion. Gas products analysis showed a large amount of CO and CO2 instead of CH4 and H2 O during the flame burning, which suggested that extra gasification reaction, where CO as product, supported the existence of flame. Moreover, the plasma generated by the violent discharge further expanded the range of the flame, with clear spectral peaks at 589 nm, 766 nm, and 770 nm. In addition, the distribution of coke in the mixture for effective ignition was also discussed. This study may provide a new idea for the application of low volatile coals.